Determinação de herbicidas usados no cultivo de arroz irrigado na região sul do estado de Santa Catarina através da SPME-GC-ECD Determination of herbicides used in irrigated rice cultivation in the south of Santa Catarina using SPME-GC-ECD - Léa L. F. Costa; Ernani S. Sant'ana; Eliane A. Suchara; Vanira S. Benato; Eduardo Carasek (Química Nova, 2008)
Evaluation of the pollution by the herbicides alachlor, propanil and atrazine in water samples from four rivers in the cities of Turvo and Meleiro, south of Santa Catarina State, was made using the SPME-GC-ECD method. The proposed method was optimized and validated. The correlation coefficients were higher than 0.997 and linear ranges of the analytical curves were 0.1-4; 0.1-2.5 and 0.1-5 µg L-1 for atrazine, alachlor and propanil, respectively. The herbicides were quantified by GC-ECD and identified by GC-MS. Both of the selected rivers presented contamination by at least one of the studied herbicides.